Efektifitas Pemberian Suplementasi Zinc dalam Mengatasi Diare pada Anak: Literature Review - Meivita Dewi Purnamasari; Devi Oktavia Anisa (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Introduction. Diarrhea is one of the leading causes of death in children. Diarrhea is a disease characterized by increasing frequency defecation of more than three times a day with a change in stool consistency to liquid. When diarrhea occurs fluid and electrolyte loss for that effort is done by providing zinc supplementation.Objective. To identify the effectiveness of zinc supplementation in overcoming diarrhea in children.Method. journal article search is done by using electronic tool with internet connection like some database, that is: Pubmed, Google Scholar. Keywords used are